Alasan dan Implikasi Penilaian Ulama’ Hadis Terhadap Pendongeng (Al-Quṣṣās) serta Orang Soleh (Al-Ṣālihīn): Reasons and Implications of Criticism by Hadith Scholars Towards Storytellers (al-Quṣṣās) and Pious Individuals (al-Ṣālihīn)) - Yahya, Yuniar Indra; Ali, Umar; Khamim (Journal Of Hadith Studies, 2024)
The storytellers (quṣṣāṣ) and righteous individuals (al-Ṣāliḥīn) are among those who frequently narrate hadiths, but Nawawi in the introduction of Sahih Muslim doubts the authenticity of their narrations, as they are considered to often fabricate hadiths. Therefore, this article will attempt to answer how the criteria for storytellers (quṣṣāṣ) and righteous individuals (al-Shalihin) are viewed by hadith scholars and the implications of both on hadith criticism. Through literature review, whether through classical texts, journals, or relevant books on the topic, the author found that there are two typologies of storytellers: the official storytellers (al-qussas al-rasmi) and the unofficial storytellers (al-qussas tatahwwu’i syakhsyi). Meanwhile, the role of the righteous individuals (al-Ṣāliḥīn) here is portrayed as spreading the fabrications of the storytellers (al-Quṣṣāṣ).